DETERMINANT OF CUSTOMER LOYALTY AT BANK SYARIAH INDONESIA - Nik Amah; Annisatul Khoiru Maghfiroh; Anissa Ayera (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of Service Quality, Trust and Customer Satisfaction on Customer Loyalty (Case Study at Bank Syariah Indonesia). The population was all customers of Bank Syariah Indonesia Branch Madiun. The sample selection used a random sampling technique and was calculated based on the Slovin formula. The number of samples is 100. The data used is primary data. Multiple linear regression analysis was used to analyze the data. The results showed that the variables of service quality and trust partially had no effect on customer loyalty. The satisfaction variable has a significant effect on customer loyalty.